Comportamento estrutural de carcaça intertravada de dutos flexíveis sob tração - Azevedo, Nathalia França de (2018)
Flexible subsea pipes for hydrocarbon transport are multi-layered structures, where each layer moves independently, in a complex interaction. Through the operation period, these structures can be subjected to many failure modes, resulting in accidents with catastrophic consequences. The objective of this work is to study the structural behaviour of the interlocked carcass under tensile axial load. This failure mode is still little known by the industry, with few occurrences in high pressure/high temperature applications. The carcass failure mechanism under axial load is the unlocking of the interlocked profile, in a process of elastoplastic deformation substantially influenced by the structure’s geometry and by the material used in fabrication. Numerical models and experimental methods were developed, using commercial pipe samples taken out from operation, in order to better understand the problem and to determine the structure capacity to resist to such loading condition.